Toward a hyperventilation detection system in freediving: a proof of concept using force sensor technology - Pernett, Frank; Mulder, Eric; Johansson, Filip; Sieber, Arne; Bermudez, Ricardo; Lossner, Marcus; Schagatay, Erika (Frontiers in Physiology, 2025)
Background and aimHyperventilation before breath-hold diving (freediving) is widely accepted as a risk factor for hypoxic syncope or blackout (BO), but there is no practical way to address it before dives. This study explores the feasibility of using a force sensor to predict end-tidal carbon dioxide (PETCO2) to assess hyperventilation in freedivers.Methods and resultsTwenty-one freedivers volunteered to participate during two national competitions. The divers were instructed to breathe normally and perform three dry apneas of 1, 2, and 3-min duration at 2-min intervals in a sitting position. Before and after the apneas, PETCO2 was recorded. The signal from the force sensor, attached to a chest belt, was used to record the frequency and amplitude of the chest movements, and the product of these values in the 60 s before the apnea was used to predict PETCO2. The mean PETCO2 was below 35 mmHg before all apneas. The mean amplitude of the signal from the force sensor increased from apnea 1 to apnea 3 (p < 0.001), while the respiratory rate was similar (NS). The product of the respiratory rate and amplitude from the force sensor explained 34% of the variability of the PETCO2 in the third apnea.ConclusionThis study shows that a force sensor can estimate hyperventilation before static apnea, providing a basis for further research. More studies are needed to confirm its effectiveness in preventing issues. Freedivers may hyperventilate without noticing it, and such a system could improve awareness of this condition. Additional underwater tests are essential to determine whether this system can enhance safety in freediving.